Controlled Exfoliation of Layered Silicate Heterostructures into Bilayers and Their Conversion into Giant Janus Platelets. Issue 26 (3rd May 2016) - Stöter, Matthias; Gödrich, Sebastian; Feicht, Patrick; Rosenfeldt, Sabine; Thurn, Herbert; Neubauer, Jens W.; Seuss, Maximilian; Lindner, Peter; Kalo, Hussein; Möller, Michael; Fery, Andreas; Förster, Stephan; et al.
Abstract: Ordered heterostructures of layered materials where interlayers with different reactivities strictly alternate in stacks offer predetermined slippage planes that provide a precise route for the preparation of bilayer materials. We use this route for the synthesis of a novel type of reinforced layered silicate bilayer that is 15 % stiffer than the corresponding monolayer. Furthermore, we will demonstrate that triggering cleavage of bilayers by osmotic swelling gives access to a generic toolbox for an asymmetrical modification of the two vis‐à‐vis standing basal planes of monolayers. Only two simple steps applying arbitrary commercial polycations are needed to obtain such Janus‐type monolayers. The generic synthesis route will be applicable to many other layered compounds capable of osmotic swelling, rendering this approach interesting for a variety of materials and applications. Abstract : Controlled exfoliation of layered silicate heterostructures into bilayers with unprecedented precision by osmotic swelling gives access to a general method for asymmetrical modification of basal planes. Only two simple steps are needed to obtain Janus‐type monolayers as bulk material.